Value chain analysis and market factors of pineapple (Ananas comosus L. Merr.) productions in Johor, Malaysia - Jaji, Khadijat (2016)
Pineapple (Ananas comosus L. Merr.) is a tropical, perennial, and economically important fruit with encouraging market potential in the global market. It is the first crop grown as a commodity crop in Malaysia and raised the country’s position to a very significant level in the world between the late 60s and early 70s. However, the contribution of Malaysian pineapple to the global market in the recent time has been experiencing downward trend, resulting to a set-back in its competitiveness. Therefore, the knowledge about the series of activities, the chain actors involved from pineapple production to consumption, as well as limitations of the chain is considered necessary. Following this scenario, this study focused on value chain analysis and market factors of pineapple production in Johor, Malaysia with specific objectives to map the value chain and marketing channels of pineapple and identify the factors associated with market outlet choice of the pineapple producers; to identify factors influencing pineapple market supply; and to determine the most influencing factors affecting quantity of pineapple supply. A cross-sectional study design was adopted in this study. A well-structured close ended questionnaire via face-to face survey was used to collect primary data from 170 farmers, 20 wholesalers, 30 retailers, and 6 processors. Both descriptive and inferential statistics were used to analyze the data. Descriptive statistics was used to map pineapple value chain and marketing channels. Factors affecting pineapple supply was identified using factor analysis, while multiple regression analysis was employed to determine the most influencing factors affecting quantity of pineapple supplied by the farmers. Based on descriptive statistics, the value chain and marketing channels map showed that the major actors in the study area are pineapple producers, assemblers, wholesalers, FAMA, retailers, processors, exporters, and consumers. The choice of marketing channels by pineapple farmers in the study area was based on the factors such as price of product, grading, timely payment, and mode of payment respectively. The result also revealed that pineapple value chain is constrained by lack of access to credit, high inputs price, shortage of labor, unfair price quotation, poor market information, high transport cost, lack of demand, aging farmers, and poor chain governance. Six (6) factors identified as the factors affecting pineapple supply using factor analysis are credit access, pineapple varieties, distance to the market, cost of inputs, price of pineapple and extension services. Quantity of pineapple supplied was found affected positively by farming experience, farm size, credit access, pineapple variety, cost of inputs, price of pineapples, and extension services at 5%, 1%, 1%, 5%, 1%, 5% and 5% significant level respectively. Therefore, this study recommends the need for designing appropriate intervention mechanisms focusing on the aforementioned factors to improve the status of pineapple value chain and uplift the smallholder pineapple farmers.